1998
DOI: 10.1002/hep.510280412
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of OV-6, a putative progenitor cell marker in human fetal and diseased pediatric liver

Abstract: The existence of progenitor (stem) cells in the human liver remains a matter of debate. In rodent models of hepatocarcinogenesis and injury, oval cells proliferate in the periportal regions of the portal tracts and are suggested to derive from a stem cell compartment, because they are capable of differentiating into hepatocytes or biliary epithelial cells. In this study, the rat oval cell marker, OV-6 has been used to investigate the hypothesis that there are stem cells present in fetal and pediatric human liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 16 publications
8
82
2
Order By: Relevance
“…Despite that OV-6 was positive in some bile duct cells that always shared immunoreactivity for CK19 in cirrhotic liver, OV-6 was regarded as a specific marker of liver progenitor cells that have the capacity to differentiate into either hepatocytes or biliary cells. 8,[17][18][19][20][21] Moreover, increasing evidence indicated that HCC with ICC differentiation was derived from a hepatic progenitor cell. 4,17,20 During its neoplastic transformation the progenitor cell marker (OV-6) and biliary marker (CK19) could partially be retained in HCC cells, 6 which resemble hepatic progenitor cells with coexpression of CK19 and OV-6, 22 and was consistent with the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that OV-6 was positive in some bile duct cells that always shared immunoreactivity for CK19 in cirrhotic liver, OV-6 was regarded as a specific marker of liver progenitor cells that have the capacity to differentiate into either hepatocytes or biliary cells. 8,[17][18][19][20][21] Moreover, increasing evidence indicated that HCC with ICC differentiation was derived from a hepatic progenitor cell. 4,17,20 During its neoplastic transformation the progenitor cell marker (OV-6) and biliary marker (CK19) could partially be retained in HCC cells, 6 which resemble hepatic progenitor cells with coexpression of CK19 and OV-6, 22 and was consistent with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…8,[17][18][19][20][21] Moreover, increasing evidence indicated that HCC with ICC differentiation was derived from a hepatic progenitor cell. 4,17,20 During its neoplastic transformation the progenitor cell marker (OV-6) and biliary marker (CK19) could partially be retained in HCC cells, 6 which resemble hepatic progenitor cells with coexpression of CK19 and OV-6, 22 and was consistent with the present study. Therefore, CK19(1) HCC represents a distinct type of HCC with ICC-like differentiation with an increased risk for developing LNM.…”
Section: Discussionmentioning
confidence: 99%
“…52 Evidently, this situation also occurs in humans, as elevated levels of serum HGF are present in individuals with chronic hepatitis and cirrhosis, [55][56][57] both conditions in which oval cell proliferation is well documented. 7,18,38,40,58,59 In situ hybridization has revealed that oval cells and basophilic hepatocytes, in addition to hepatic stellate cells, express aFGF transcripts. 60 A marked increase in hepatic aFGF levels has been reported at the peak of oval cell proliferation in the 2-AAF/PH model, and levels greatly exceeded those observed after PH alone, suggesting a more prominent role for aFGF in oval cellmediated regeneration.…”
Section: Role Of Hepatic Stellate Cellsmentioning
confidence: 99%
“…They were further divided into two groups retrospectively according to the clinical features at the end of 12-month follow-up after the Kasai operation: three patients (patients 6-8) who were jaundice free and with good bile flow (BA1) and six patients (patients 9-14) who had jaundice and finally underwent liver transplantation (BA2). In addition, liver tissues were also obtained from six children (Supporting Table 1, patients [15][16][17][18][19][20] with advanced-stage BA at the time of liver transplantation (LT). Near-normal liver tissues were the nontumor parts of surgically removed liver tissues from two patients with colon cancer metastasized to the liver.…”
Section: Methodsmentioning
confidence: 99%
“…15 Striking similarities have been reported between proliferative bile ductules and developing bile ducts in human fetus. 16 Because there are increased numbers of both proliferating ductular cells and newly regenerating hepatocytes in BA livers, 17 it has been suggested that both types of cells may differentiate from HSCs activated in BA livers. 17 Based on these observations, here we explored the mechanisms controlling the activation and differentiation of cells in ductular reactions and their possible relationship to HAI-1 and -2-related ECM remodeling and fibrosis progression in livers with BA or other cholangiopathies.…”
mentioning
confidence: 99%